Adolescent muscle dysmorphia and family-based treatment: A case report. (April 2015) - Murray, Stuart B; Griffiths, Scott
A growing body of evidence suggests that the prevalence of male body dissatisfaction and muscle dysmorphia is rising. To date, however, there is no published evidence on the efficacy of treatments for muscle dysmorphia. We present the case of a 15-year-old boy who met full diagnostic criteria for muscle dysmorphia, whose symptoms were treated into remission with eating disorder-focused, family-based treatment. The age of this patient fell within the time period in which symptoms of muscle dysmorphia are most likely to develop and this case represents the first published case report of family-based treatment for muscle dysmorphia in this age group. Thus, this case report has important implications for clinicians considering treatment options for presentations of muscle dysmorphia when first presenting in adolescence. Implications for the development of treatment guidelines for muscle dysmorphia and for the diagnostic debate surrounding muscle dysmorphia are also discussed.